Sentidos da vivência educativa para adultos maduros de uma turma de educação de jovens e adultos - Conzatti, Fernanda de Brito Kulmann (2015)
This research of qualitative approach used the collective case study method and aimed to understand the meanings that the mature adult learners of EJA educational modality – from Portuguese, “Educação de Jovens e Adultos”– attributed to the resumption of formal education as well as their perceptions of the changes from this educational method. The sample consisted of four adult learners, regulars of the second year of high school, the Youth and Adults Educational Modality (EJA), a school institution of the federal public schools of Porto Alegre/Rio Grande do Sul, in the age group between 47 and 68 years, civil servants of a federal institution of higher education and recipients of scholarship. The data collection was carried out in the school attended by the thesubjects of this study, through semi-structured interview, recorded on audio and later transcribed by the researcher; building a timeline of the history of the students investigated; observations in the classroom; consultation and analysis of the political-pedagogical project of the educational institution for adult education. For data analysis was used Discursive Textual Analysis (DTA), based especially on Bioecological Theory of Human Development. The results pointed to the emergence of two categories: educational experiences in the EJA modality and nuisances caused by the educational process in adult education, way of revealing the universe experienced by the subjects in formal education and that reverberated in various spheres and contexts of their lives. These senses were guided up by motivations, difficulties, existence of a network of social and emotional support to stay in EJA, future expectations as well as changes manifested in cognitive spheres, behavioral, psychosocial and lifestyle habits of respondents. The production of meanings for the subjects was mediated by constant intercommunication between Micro, Meso,Exo and macro systems, represented by the mutual relations and the social and emotional support in the resumption of the formal education process. Moreover, they accounted for healthy development processes, with cognitive changes, behavioral, psychosocial and positive lifestyle habits in the lives of respondents. The theoretical perspective adopted intended to bring a new bias in the approach to the adult learners who seek adult education beyond any stigma or prejudice in seeking other components of this type of education, and especially the education of mature adults, overtaking its understanding only from the educational perspective, guided by the principles of repair, qualification and equalization. The intention was to bring to discussion aspects that reflected in a significant and latent way, the lives and backgrounds of these people, from transforming experiences in a systematic and continuous approach to development. Also, highlighting the importance of a network of social and emotional support in this dynamic where different processes, people and contexts articulate, in an attempt to allow forms and ways for all people, regardless of age, experience situations that empower changes in their lives.